Mental health of UK youth following the removal of the Education Maintenance Allowance in England: a natural experiment study using Understanding Society data - Srinivasa Vittal Katikireddi; Richard John Shaw; Andrew James Baxter (BMJ Public Health)
Background The Education Maintenance Allowance (EMA) encourages people in low-income households to stay in education. It was abolished in England but continues in the rest of the UK (RUK). We investigated if the abolition of the EMA was associated with psychological distress using a difference-in-difference design.Methods The sample of 1328 observations was drawn from Understanding Society participants aged 16/17 at the start of the academic years 2009–2018 and in the bottom income decile. Exposure to the EMA policy regime was identified using an interaction between the UK area (RUK vs England) and EMA policy period. The 2009/2010 academic years indicated the EMA period, 2011 the transition period (when EMA receipt was limited to existing recipients) and 2012–2018 post-EMA. The primary outcome was the General Health Questionnaire-12 (GHQ-12) score ranging 0–36. Other outcomes include the 12-item Short-Form Health Survey (SF-12) and a physical health falsification outcome. Linear regression using robust SEs, adjusting for sex and month of interview, was conducted.Results In England, relative to RUK and the EMA period, the transition period (Coef 4.20; 95% CI 1.12 to 7.28) and the post-EMA period (Coef 2.89; 95% CI 0.67 to 5.11) were associated with worse GHQ-12 scores. Results for other mental health outcomes were similar, with no associations with the falsification outcome.Conclusions Young people living in low-income households in England appeared to have worse mental health following the removal of the EMA, compared with RUK. However, it is not possible to rule out the potential contribution of cointerventions, such as the raising of mandatory age for education to 17 years in 2013 and 18 years in 2015.